Soil and climatic characteristics and farming system shape fungal communities in European wheat fields - Peltoniemi, Krista; Velmala, Sannakajsa; Lloret, Eva; Ollio, Irene; Hyvönen, Juha; Liski, Eero; Brandt, Kristian K.; Campillo-Cora, Claudia; Fritze, Hannu; Iivonen, Sari; Lassen, Simon B.; Loit, Kaire; et al. (Elsevier, 2024)
Fungi play a pivotal role as highly effective decomposers of plant residues and essential mycorrhizal symbionts, augmenting water and nutrient uptake in plants and contributing to diverse functions within agroecosystems. This study examined soil fungi in 188 wheat fields across nine European pedoclimatic zones under both conventional and organic farming systems, utilizing ITS1 amplicon sequencing. The investigation aimed to quantify changes induced by the farming system in soil fungi and their correlation with soil features and climatic factors across these pedoclimatic zones, spanning from northern to southern Europe. The pedoclimatic zone emerged as a key determinant in shaping the overall composition of the fungal community. Zones characterized by moist and cool climates, along with low levels of available phosphorus and carbonate, exhibited higher fungal richness. However, variations in fungal diversity and relative abundances were observed within zones due to farming system-induced changes. Soil pH and bulk density were identified as major factors, for example, they correlate with an increase in potential pathogenic taxa (Mycosphaerella, Nectriaceae, Alternaria) in two Mediterranean zones and with an increase of potential plant growth promoting taxa (Saitozyma, Solicoccozyma) in the Boreal zone. Organic farming, in general, promoted elevated fungal richness. The Lusitanian and Nemoral zones under organic farming exhibited the highest fungal richness and diversity. In terms of organic farming, both symbiotrophs and potential pathogens increased in the Lusitanian zone, while pathotrophs were more prevalent in the Central Atlantic and South Mediterranean zones under organic farming. These findings propose potential indicators for organic farming, including fungal endophytes in zones characterized by a moist and cool climate, low available phosphorus content, and low soil pH. Organic farming may favor mycorrhizae and potential pathogens in zones with drier and warmer climates, along with higher soil pH, calcium carbonate content, and bulk density. This study provides novel insights and underscores the significance of regional climatic and edaphic conditions in shaping the soil fungal community in different farming systems within European wheat fields.
Keywords: fungi; wheat field; conventional farming; organic farming; farming system